1973
DOI: 10.1111/j.2153-3490.1973.tb01597.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of atmospheric radioactivity at Ibadan

Abstract: The results of regular monitoring of air samples for radioactivity at Ibadan for the period July 1966 to February 1967 are presented here. The results show a general increase of atmospheric specific radioactivity and particular periods of high atmospheric specific radioactivity during the Harmattan season. The general increase in atmospheric specific activity is not correlated with nuclear weapons tests and is explained in terms of the enhanced exhalation of emanation from the earth's crust. The prominent peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…some industrial activities and materials may contain significant quantities of NORM that may lead to an increase in activity concentrations of radionuclides and background radiation Altering geological radioactive materials from their natural setting may result in relative increase in radiation exposure and health risks to the public (Agalga et al, 2013). Also, it has been reported that in some cases much above recommended safe level (Sanni, 1973, Avwiri and Ebeniro, 1998and Nwankwo and Akoshile, 2005.…”
Section: Introductionmentioning
confidence: 97%
“…some industrial activities and materials may contain significant quantities of NORM that may lead to an increase in activity concentrations of radionuclides and background radiation Altering geological radioactive materials from their natural setting may result in relative increase in radiation exposure and health risks to the public (Agalga et al, 2013). Also, it has been reported that in some cases much above recommended safe level (Sanni, 1973, Avwiri and Ebeniro, 1998and Nwankwo and Akoshile, 2005.…”
Section: Introductionmentioning
confidence: 97%
“…Ayo et al [1] suggest that investigation should be conducted into substitute local flour sources for baking, such as millet, sorghum, cassava, African breadfruit, plantain, acha, and many more, due to the nation's limited capacity to provide the nation's high demand for wheat flour. Utilized in baking, snacking, and supplementary food formulations, composite flour derived from plantain, cassava, soybean, and other locally grown crops [2]. Attempts have been made to promote the incorporation of composite flour, which completely or partially substitute wheat flour in baked goods with flours derived from locally cultivated crops with highprotein seeds.…”
Section: Introductionmentioning
confidence: 99%